PERFORMANCE OF PARENTS AND HYBRIDS FOR YIELD AND YIELD ATTRIBUTING CHARACTERS IN RIDGE GOURD (LUFFA ACUTANGULA (ROXB.) L.) - REDDY, P. KARTHIK; V. S. K. REDDY,; S. S. VIJAYA PADMA, (The Bioscan, 2013)
The present study was carried out to know the performance of hybrids and their parents for the sixteen quantitative traits attributing for yield in ridge gourd. Among the parents used for investigation T1, T3 and L4 were high yielding of 1.36, 1.09 and 1.07 kg per vine, respectively. The promising hybrids L4 x T1, L5 x T1 and L1 x T2 recorded high yield of 2.27, 2.16 and 1.93 kg per vine, respectively over the two commercial checks. The hybrid L4 x T1 was most promising for various traits which contribute to early and highest fruit yield per vine. The best performing parents can be used for further breeding programmes and hybrids could be exploited for cultivation.